Pengaturan Dewan Pers dalam Penanggulangan Tindak Pidana Pers pada Era Digital - ADI, KETUT ADI WIRAWAN (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
The press as one of the main pillars of democracy has an important role in delivering accurate and objective information to the public. In this context, restrictions on press freedom are regulated in the Criminal Code and other laws and regulations, including Law No. 40/1999 on the Press. This study aims to analyze in depth the criminal law arrangements in the law, considering that the changes have not kept up with the development of the digital era. This research uses a normative legal method with a legislative approach and legal concept analysis to examine the relevance of criminal law arrangements in facing the challenges of information technology. The research findings show that some of the content in Law No. 40/1999 on the Press is no longer relevant in the ever-evolving digital era, so a more adaptive regulatory reformulation is needed. In addition, the role of the Press Council in overseeing the implementation of the journalistic code of ethics and protecting journalists from criminalization needs to be strengthened. This research contributes to providing recommendations for legal policies that are more effective in tackling press crimes in the digital era. Thus, it is important to reform press regulations in order to be able to face the challenges of information globalization and maintain the integrity of press freedom in Indonesia.